Pubertal development, low self-control, and violence among South Korean girls - Kweon, Haesoo (International journal of law, crime and justice, 2018)
The literature on the low self-control theory hints that low self-control may interact with other risk factors to generate antisocial behaviors. A separate line of the literature on pubertal timing indicates that pubertal development may interact with criminogenic factors to produce adolescents' violent behaviors. Juxtaposing these two literature that have been rarely linked in empirical research, the present study examines a hypothesis in the field of criminology that self-control interacts with pubertal timing in the creation of violent acts among adolescent girls. Using a cross-sectional sample of South Korean girls, the results of the analysis support the working hypothesis that girls' violent acts are amplified by the combination of low self-control and early pubertal development. Based on the results, implications for research and policy are discussed.